The effectiveness of using food fun facts to increase acceptance of new menu items among children attending a childcare center: a pilot study - Guthrie, Grace Gibson (Kansas State University, 2022)
Background: Childhood is a time when healthy habits can be created, but it is also a time when picky eating or unwillingness to try new foods can be a challenge. Exposure to new foods plays an important role in acceptance, and childcare centers have a unique opportunity to provide children with new food experiences. Objective: To test the effectiveness of using exposure in the form of food fun facts to increase acceptance of new menu items among children attending a childcare center. Methods: Fun facts were created to accompany two new childcare center menu items. A randomized crossover design was used to assign eight childcare classrooms to either receive or not receive pre-meal fun facts. Forty-four children were enrolled in the study, and each new menu item was served four times yielding a total of eight observation days. Researchers recorded whether or not the new food was tried during each individual meal observed (N = 289). Analysis: Chi squared analysis was used to compare the rate of food trying between observations that were preceded by the fun facts and those that were not. Results: The rate of food trying was higher (p = .015) among observations preceded by the fun facts (74.4%) compared to the observations that were not preceded by the fun facts (60.8%). Conclusion: Presenting fun facts before introducing news foods led to a higher rate of trying the foods. This finding suggests that fun facts may be a relatively easy and low-cost way of improving new food acceptance.
Keywords: Picky eating; Early childhood; Nutrition; Childcare center; Dietary diversity; Fun facts